2010
DOI: 10.1089/adt.2010.0334
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphine Oxide Is a Potent and Selective Inhibitor of the Transient Receptor Potential Melastatin-5 Ion Channel

Abstract: Transient receptor potential melastatin-5 (TRPM5) is a calcium-gated monovalent cation channel expressed in highly specialized cells of the taste bud and gastrointestinal tract, as well as in pancreatic β-cells. Well established as a critical signaling protein for G protein-coupled receptor-mediated taste pathways, TRPM5 also has recently been implicated as a regulator of incretin and insulin secretion. To date, no inhibitors of practical use have been described that could facilitate investigation of TRPM5 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…4 B and C). Although TPRM5 itself is a monovalent-specific cation channel activated by Ca 2+ rather than a Ca 2+ channel itself (18), its inhibition by triphenylphosphine oxide (TPPO) is known to significantly reduce the tastant-induced rise in [Ca 2+ ] i in mouse taste bud cells (19); we found that this action applies to denatonium responses in urethral cells as well (Fig. 4D).…”
Section: Cholinergic Urethral Brush Cells Use the Canonical Taste Tramentioning
confidence: 78%
“…4 B and C). Although TPRM5 itself is a monovalent-specific cation channel activated by Ca 2+ rather than a Ca 2+ channel itself (18), its inhibition by triphenylphosphine oxide (TPPO) is known to significantly reduce the tastant-induced rise in [Ca 2+ ] i in mouse taste bud cells (19); we found that this action applies to denatonium responses in urethral cells as well (Fig. 4D).…”
Section: Cholinergic Urethral Brush Cells Use the Canonical Taste Tramentioning
confidence: 78%
“…Because the LA-induced TRP-like inward currents were selective for monovalent cations, we investigated the possibility of TRPM5 involvement in LA-induced signaling in STC-1 cells. TPPO, a specific antagonist for TRPM5 (19), significantly reduced LA-induced and, importantly, denatonium benzoate-induced inward currents. We saw very similar levels of inhibition of LA-induced and denatonium benzoate-induced inward currents upon application of TPPO.…”
Section: Discussionmentioning
confidence: 96%
“…TRPM5, as well as GPCR taste receptors and other G protein signaling elements, is expressed in STC-1 cells (4, 16, 21). On the basis of our results that LA-activated currents in STC-1 cells are primarily monovalent cation selective, we investigated specific involvement of TRPM5 channels in LA-activated inward current by using the TRPM5 channel blocker triphenylphosphine oxide (TPPO) (17,19). In whole cell voltage-clamp experiments, we compared LA-induced inward currents in control STC-1 cells and in TPPO-treated (100 M, 2-min pretreatment) STC-1 cells.…”
Section: La Activates Sodium-dependent Inward Currents In Stc-1 Cellsmentioning
confidence: 99%
“…Furthermore, denatonium-induced calcium responses were blocked by inhibition of PLCβ2 (Supplemental Figure 3A), an important downstream component of taste signal transduction (18). The duration of denatonium-induced calcium responses was reduced by either removal of extracellular calcium or application of triphenylphosphine oxide (Supplemental Figure 3B), an inhibitor of the TRPM5 component of taste signaling (19). Additionally, the inositol triphosphate receptor (IP 3 R) inhibitor xestospongin B significantly inhibited the denatonium-induced calcium response (Supplemental Figure 3C).…”
Section: T2r Agonists Activate Localized Calcium Signals In Human Sinmentioning
confidence: 99%